Epidemiology of Canine Mast Cell Tumors in Uruguay - Denis, Alex; Yamasaki, Kanji; Cruz, Juan Carlos; Verdes, José Manuel (Brazilian Journal of Veterinary Pathology, 2020)
We examined in the present study main epidemiological features of canine mast cell tumors in Uruguay, principal breeds of occurrence, age, gender, anatomical distributions, and associated differences of pathological grading. During a three-year period, eighty four out of 405 skin specimens of dogs mainly received at the Veterinary Faculty of Montevideo from private clinics were mast cell tumors. Mix-breed dogs were mostly affected, followed by Labrador Retrievers, Boxers, Pit bulls and Golden Retrievers. Age of patients ranged from 3 to 15 years (median 7.9), and the incidence in females was slightly higher than in males. Tumors were more frequent in the trunk, followed by extremities, scrotum and neck. The majority of specimens were of high malignancy.